O processo de cessação do fumar na perspectiva de ex-fumantes - Silva, Cremilda Maria de Mello (2005)
This study aims to understand how individuals live and elaborate the stopping smoking process in their social contexts, beginning with former-smokers' experiences. The smokers go through motivational stages, until they manage to stop smoking, which for some can be a short time while for others, takes years. The stage change is influenced by several factors. It can be seen, among these, that the stopping smoking stage occurs due to present forces in the societies which aim to control tabaccoism, as well as, from cultural factors that promote smoking abstention indirectly. This last one being attributed, to the fact that tabaccoism as a practice does suit the current conceptions of health, beauty and well being. A qualitative study with carried out on individuals that had stopped smoking for at least one year and were being attended by the Prevention State Reference and Tabaccoism Treatment Center (CREPTT). 17 subjects (11 women and 6 men) with ages ranging from 36 to 71 years were interviewed. The empiric data obtained from interviews from former smokers were analyzed according to Content Thematic Analysis and interpreted according to the Social Representations Theory. The most important considerations are as follows: stopping smoking was shown to be an awareness process of perceiving tabaccoism as a problem of the individual and the people close to him or her. Factors related to the body and social coexistence contributed to the search for recovery from tabaccoism. The experience links, interpreted as abstinence supports, were the interpersonal network of relatives, professionals and treatment group colleagues, contact with former-smokers, determination and faith. Tabaccoism abstention was associated to changes. These changes, were perceived as conditions for a better life. Tabaccoism abstention by the former-smokers of this study is seen, to be the condition, among others, of feeling healthier, with a better physical appearance and social acceptance.